Evaluation of a delirium awareness podcast for undergraduate nursing students in Northern Ireland: a pre−/post-test study - Gary Mitchell; Jessica Scott; Gillian Carter; Christine Brown Wilson (BMC, 2021)
Abstract Background Delirium is a common disorder affecting several people in primary, secondary, and tertiary settings. The condition is frequently under-diagnosed leading to long-lasting physical and cognitive impairment or premature death. Despite this, there has been limited research on the impact of innovative approaches to delirium education amongst undergraduate nursing students. The aim of this study was to evaluate the effect of a delirium awareness podcast on undergraduate nursing student knowledge and confidence related to the condition in Northern Ireland. Methods The intervention was a 60-min delirium awareness podcast, available throughout May 2020, to a convenience sample of year one undergraduate nursing students (n = 320) completing a BSc Honours Nursing degree programme in a Northern Ireland University. The podcast focused on how nursing students could effectively recognise, manage, and prevent delirium. Participants had a period of 4 weeks to listen to the podcast and complete the pre and post questionnaires. The questionnaires were comprised of a 35-item true-false Delirium Knowledge Questionnaire (DKQ), a 3-item questionnaire about professional confidence and a 7-item questionnaire evaluating the use of podcasting as an approach to promote knowledge and confidence about delirium. Data were analysed using paired t-tests and descriptive statistics. Results Students improved across all three core areas in the post-test questionnaire, demonstrating improvements in knowledge about symptoms of delirium (7.78% increase), causes and risk factors of delirium (13.34% increase) and management of delirium (12.81% increase). In relation to perceived confidence, students reported a 46.50% increase in confidence related to recognition of delirium, a 48.32% increase in relation to delirium management and a 50.71% increase their ability to communicate about delirium. Both questionnaires were statistically significant (P < 0.001). The final questionnaire illustrated that nursing students positively evaluated the use of podcast for promoting their knowledge and confidence about delirium and 96.32% of nursing students believed that the podcast met their learning needs about delirium. Conclusions A 60-min podcast on delirium improved first year student nurse knowledge about delirium. Nursing students also expressed that this approach to delirium education was effective in their learning about the condition.